Efforts to Improve Children's Ability to Recognize Letters Through the Use of Letter Card Media in AR-RIDHO Kindergarten, Jambi City - Rumaisyah, Alfiya (USN Kolaka, 2024)
This research aims to improve children's ability to recognize letters through letter card media in AR-RIDHO Kindergarten, Jambi City. In its implementation, there are two cycles of this research: actions in classroom action research. Kindergarten in Group B AR-RIDHO as research participants, totalling nine students. The second semester of the 2023/2024 academic year was used for this investigation. Observation is the approach used to obtain data. The observation sheet is the instrument used in this research to collect data. Utilizing qualitative descriptive data analysis. A child's proficiency in letter recognition is said to have increased if the proportion of the child's proficiency reaches 88.89% with suitable criteria. Children's pre-action letter recognition skills meet the criteria of not being good, with an average increase in letter recognition of 58.65%. The children's average score of 77.22% in cycle I show they can recognize letters, meeting the required criteria. The second action cycle was necessary because, although there had been improvements after the first, children's letter recognition skills still needed to reach the mark of success. According to Cycle II data, the average child's letter recognition is 88.89%, which is good.